2007
DOI: 10.1007/s00784-007-0100-9
|View full text |Cite
|
Sign up to set email alerts
|

Dental erosion in chronic renal failure

Abstract: Dental erosion is a common oral finding in chronic renal failure and may develop due to extrinsic and/or intrinsic causes. The aim of this study was to compare the salivary calcium and phosphorus levels, salivary flow rate, salivary buffer capacity, salivary pH, serum calcium and phosphorus levels and parathyroid hormone levels in chronic renal failure patients with and without dental erosion. Twenty-four men and 19 women who had had chronic renal failure for at least 2 years were studied. Twenty-two subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
2
7
1
5
Order By: Relevance
“…O uso de balas duras estimula a produção de saliva o que pode contribuir para a diminuição da erosão 43 .…”
Section: Resultados O Doença Renal Crônicaunclassified
“…O uso de balas duras estimula a produção de saliva o que pode contribuir para a diminuição da erosão 43 .…”
Section: Resultados O Doença Renal Crônicaunclassified
“…A major problem for the condition of the dental organ is the occurrence of renal osteodystrophy [4]. Furthermore, previous studies have shown that in patients with chronic renal failure, increase in serum phosphorus level, serum PTH level and salivary phosphorus level induces the formation of dental cavities [5]. Latest reports also analyze the relationship between the level of urea in the serum and the quality of the oral environment [6].…”
mentioning
confidence: 99%
“…As alterações da saliva compreendem alterações na sua composição e diminuição do fluxo salivar. A xerostomia poderia também aumentar o risco de cáries cervicais (BOTS et al, 2007;CASTILLO et al, 2007;IMIRZALIOGLU et al, 2007;ROBERTS, 2005;MARTINS et al, 2006;PROCTOR et al, 2005;SHARMA;PRADEEP, 2007 O hiperparatireoidismo secundário também poderia estar relacionado com alterações periodontais ao destruir tecido ósseo produzindo um alargamento do ligamento, muitas vezes com severa destruição periodontal e mobilidade dentária (PROCTOR et al, 2005).…”
Section: Manifestações Oraisunclassified
“…O hiperparatireoidismo secundário afeta 92% dos pacientes que recebem tratamento de hemodiálise (PROCTOR et al, 2005;IMIRZALIOGLU et al, 2007).…”
Section: Alterações óSseasunclassified
See 1 more Smart Citation